Global, regional, and national trends for childhood myocarditis from 1990 to 2021: health inequality and age-period-cohort analysis for the Global Burden of Disease Study 2021 - Fang, Hui-Juan; Liu, Bao-Peng; Han, Bo; Tian, Jie (Frontiers in Pediatrics, 2025)
BackgroundChildhood myocarditis (CM) may have a profound impact on lifelong health worldwide. This study aimed to assess the trends and explore the health inequality along with age–period–cohort (APC) analysis for CM from 1990 to 2021.MethodsThis study is based on the database for Global Burden of Disease (GBD) 2021. The age-standardized rate (ASR) of incidence, prevalence, mortality, and disability-adjusted life years (DALYs) was used to assess CM burden. Estimated annual percentage changes (EAPC) in ASR from 1990 to 2021 were used to calculate the time trends. Health inequalities related to the sociodemographic index (SDI) and APC effect for CM burden were studied in this study.FindingsA significant decreasing trend for ASR of incidence, prevalence, mortality, and DALYs from 1990 to 2021 was found for CM globally. The increased EAPC of prevalence for CM was still high in high SDI regions. Higher ASR of prevalence and incidence and lower ASR of mortality and DALYs were significantly associated with higher SDI levels. A significant increase in SDI-related health inequalities was found from 1990 to 2021 for ASR prevalence. Higher risk for CM prevalence was found in the younger ages, recent periods, and birth cohort among high SDI regions. Non-optimal temperature was also significantly associated with elevated risk of mortality and DALYs for CM.InterpretationAlthough CM burden has been decreasing in recent years, the disproportionate CM burden globally warrants caution. Effective methods should be used to decrease CM burden in the future.